Understanding and Being Understood: Information and Care Needs of 2113 Patients With Confirmed or Suspected COVID-19. (5th March 2021) - Houben-Wilke, Sarah; Delbressine, Jeannet M; Vaes, Anouk W; Goërtz, Yvonne MJ; Meys, Roy; Machado, Felipe VC; Van Herck, Maarten; Burtin, Chris; Posthuma, Rein; Franssen, Frits ME; van Loon, Nicole HP; Hajian, Bita; et al.
To become a proactive and informed partner in postacute coronavirus disease 2019 (COVID-19) management, patients need to have the knowledge, skills, and confidence to self-manage COVID-19-related health challenges. Due to several restrictions and consequently social isolation, online platforms and forums where people can share information and experiences became more popular and influential. Therefore, this study aimed to identify perceived information needs and care needs of members of 2 Facebook groups for patients with COVID-19 and persistent complaints in the Netherlands and Belgium and patients with COVID-19 who registered at a website of the Lung Foundation Netherlands. Besides demographics and clinical characteristics, the degree of satisfaction with care during and after the infection as well as satisfaction with available information were assessed. Open text fields revealed specific information needs which were summarized. Patients with confirmed or suspected COVID-19 perceive various unmet needs varying from specific information needs (eg, information about permanent lung damage) to general needs (eg, being heard and understood). These data lead to several recommendations to improve care for patients with COVID-19 and justify further development of online platforms specifically addressing these unmet needs.